2012
DOI: 10.4161/cc.22778
|View full text |Cite
|
Sign up to set email alerts
|

Dietary downregulation of mutant p53 levels via glucose restriction

Abstract: The majority of human tumors express mutant forms of p53 at high levels, promoting gain of oncogenic functions and correlating with disease progression, resistance to therapy and unfavorable prognosis. p53 mutant accumulation in tumors is attributed to the ability to evade degradation by the proteasome, the only currently recognized machinery for p53 disruption. We report here that glucose restriction (GR) induces p53 mutant deacetylation, routing it for degradation via autophagy. Depletion of p53 leads, in tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
122
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(126 citation statements)
references
References 37 publications
3
122
1
Order By: Relevance
“…It has been reported that prolonged glucose deprivation can lead to the degradation of mutant p53 through macroautophagy (Rodriguez et al 2012). However, prolonged glucose starvation has been shown to lead to reduction of autophagy (Fuertes et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that prolonged glucose deprivation can lead to the degradation of mutant p53 through macroautophagy (Rodriguez et al 2012). However, prolonged glucose starvation has been shown to lead to reduction of autophagy (Fuertes et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…16 As a consequence of the transactivation of so many different promoters so far described, p53 is able to activate different biochemical pathways affecting the regulation of life and death of the cell. A recently discovered, relevant set of novel p53 targets include the metabolism of the cell, 17,18 for example the pathways of mevalonate, 19,20 serine, 21 malate, 22 and glutaminolysis. 23 This results in the regulation of cell death 24 or cell cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Wild-type p53 is typically expressed at low levels because of its degradation via the proteasome, which is controlled mainly by the E3-ubiquitin ligase MDM2. However, mutant p53 forms, which are widely expressed in tumors, are thought to be able to evade proteolysis by blocking MDM2 transcription and causing subsequent aberrant interactions (Prives and White, 2008;Brosh and Rotter, 2009;Rodriguez et al, 2012). A recent study done by Cooks et al (Cooks et al, 2013) reported the prolongation of TNF-α-induced NF-κB activation by mutant p53 in vivo in intestinal cells.…”
Section: Micrornamentioning
confidence: 98%
“…The restriction of caloric intake displays effects at the cellular and organismal levels, altering various epigenetic mechanisms and signaling pathways Mercken et al, 2013). Rodriguez et al (Rodriguez et al, 2012) were able to show a correlation between CR, in the form of glucose restriction, and a downregulation of mutant p53, which is widely expressed in a majority of tumors. It is known that cancer cells metabolize glucose at an elevated rate compared with normal cells, and it is this phenomenon that makes glucose restriction a novel therapeutic approach in the impairment of cancer growth and progression.…”
Section: Caloric Restriction Aging and Cancermentioning
confidence: 99%
See 1 more Smart Citation